2012
DOI: 10.1371/journal.pone.0028806
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Autotoxic Compounds in Fibrous Roots of Rehmannia (Rehmannia glutinosa Libosch.)

Abstract: Rehmannia is a medicinal plant in China. Autotoxicity has been reported to be one of the major problems hindering the consecutive monoculture of Rehmannia. However, potential autotoxins produced by the fibrous roots are less known. In this study, the autotoxicity of these fibrous roots was investigated. Four groups of autotoxic compounds from the aqueous extracts of the fibrous roots were isolated and characterized. The ethyl acetate extracts of these water-soluble compounds were further analyzed and separated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
55
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 68 publications
(57 citation statements)
references
References 18 publications
2
55
0
Order By: Relevance
“…Its fresh and dried tuberous roots are used as a traditional Chinese medicinal ingredient for sedation, diabetes, haematological conditions, and insomnia [4][5][6] . The extract of its tuberous roots contains iridoids, monoterpenes, glycosides, fatty acids, amino acids, and microelements that have been reported to have various medical effects concerning reduction of blood pressure, blood circulation, immune capability, endocrine balance, and cardiovascular regulation [7][8][9] .…”
Section: Introductionmentioning
confidence: 99%
“…Its fresh and dried tuberous roots are used as a traditional Chinese medicinal ingredient for sedation, diabetes, haematological conditions, and insomnia [4][5][6] . The extract of its tuberous roots contains iridoids, monoterpenes, glycosides, fatty acids, amino acids, and microelements that have been reported to have various medical effects concerning reduction of blood pressure, blood circulation, immune capability, endocrine balance, and cardiovascular regulation [7][8][9] .…”
Section: Introductionmentioning
confidence: 99%
“…Ma et al (2005) reported that phenolic acids not only affected the amount and diversity of microbial communities in soil, but also promoted growth of soil-borne pathogens such as Fusarium oxysporum and Phytophthora. It is reported that phenolic acids were isolated from fibrous roots and rhizosphere soil of R. glutinosa and might contribute to the autotoxicity of R. glutinosa (Li et al, 2012b). Qu and Wang (2008) found that phenolic acids selectively enhance specific microbial population in soil, and lead to the development of shifted communities with differing qualitative and quantitative compositions.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies showed that rhizospheric microbial dynamics largely governed proper soil ecosystem function and had close interaction with consecutive monoculture problems (Qu and Wang, 2008;Qi et al, 2009;Wu et al, 2009;Wu et al, 2011;Li et al, 2012b;Wu et al, 2013). Crop consecutive monoculture not only alters the physical and chemical properties of the soil, but also contributes to the development of diverse microbial groups in the rhizosphere (Minh, 2005;Lin et al, 2007;Yoneyama and Natsume, 2010;Berendsen et al, 2012;Ndabamenye et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Certain stresses which disturb plant growth and development have been shown to induce alterations in the pattern of methylation of genomic DNA (Ding et al, 2014;Zhong et al, 2015). Replanting disease in R. glutinosa is thought to be largely caused by the presence of its own root exudate in the soil (Wu et al, 2011;Li et al, 2012b;Ru et al, 2014), but it has not yet been established whether this acts as an agent of epigenetic alteration.…”
Section: Introductionmentioning
confidence: 99%